Insights into Theileria transmission-blocking vaccines for East Coast fever control: A disease with an “outdated vaccination approach” - C. Ndawula, Jr; P. Emudong; N. Muwereza; C. Currà (Ticks and Tick-Borne Diseases)
Instead of using the Infection and Treatment Method (ITM)-based vaccine, is it possible to control East Coast Fever (ECF) through blocking Theileria parva transmission in ticks and cattle? This review pursues this question. It's over 100 years since Arnold Theiler (1912) first illustrated the natural ITM as a vaccination approach against ECF-cattle disease. The approach entails infecting cattle with live Theileria sporozoites and co-treatment with long-acting tetracycline. Building on the ITM principle, the “Muguga”-cocktail ECF vaccine was developed in the 1970s and it remains the only commercially available-one. Although the vaccine induces cattle-protection, the vaccination approach still raises several drawbacks. Of those, the most outstanding is the vaccine-safety. This is implied because after ITM vaccination, cattle revert to T. parva pathogen reservoirs, therefore, during blood meal-acquisition, the ticks co-ingest T. parva pathogens. Ultimately, the pathogens are further transmitted transstadial; from larvae to nymph and nymph-adults and later re-transmitted to cattle during blood-meal acquisition. Consequently, the vaccine-constituting T. parva strains are introduced and (re) spread in non-endemic/ endemic areas. Precisely, rather than eradicating the disease, the ITM vaccination-approach promotes ECF endemicity. With advent of novel vaccination approaches toward vector and vector-borne disease control, ECF-control based on ITM of vaccination is considered outdated. The review highlights the need for embracing a holistic integrative vaccination approach entailing blocking Theileria pathogen-development and transmission both in the ticks and cattle, and/or the tick-population.